Improving English Speaking Skills Through Debate Methods in Students Junior High School - Adieli Laoli (Universitas Pahlawan Tuanku Tambusai, 2021)
This study was conducted to describe the improvement of speech skills and the activeness of learners in English language development through debate methods, the implementation of this activity through Class Action Research. The study was conducted in class VII-B SMPN 2 Gunungsitoli Idanoi, which numbered 27 people. This research was conducted in the Even Semester of the Academic Year 2020/2021. Data sources in this class of research include learners, peers, researchers, and documents. The data collection techniques used are observations, tests, and questionnaires. The data analysis carried out in this study is a descriptive analysis technique that includes quantitative data and qualitative data. Quantitative data is obtained from the results of learning learners, while qualitative data is obtained from observation results. The results showed that debate methods in English learning could improve learners' ability to speak. This is seen from the observation that student activity increased from 68.63% in cycle I to 86.75% in cycle II. The final score of learners increased from 70.37 in cycle I to 88.9 in cycle II. This means that the debate method has a positive effect on improving students' speaking skills.